Scientific issues with rodent models of neuromyelitis optic spectrum disorders - Huang, Yusen; Wang, Tianwei; Wang, Fangruyue; Wu, Yujing; Ai, Jia; Zhang, Ying; Shao, Meiyan; Fang, Le (Frontiers in Immunology, 2024)
Neuromyelitis optica spectrum disorders (NMOSD) is a rare autoimmune disorder that causes severe inflammation in the central nervous system (CNS), primarily affecting the optic nerves, spinal cord, and brainstem. Aquaporin-4 immunoglobulin G antibodies (AQP4-IgG) are a diagnostic marker of the disease and play a significant role in its pathogenesis, though the exact mechanism is not yet fully understood. To develop rodent models that best simulate the in vivo pathological and physiological processes of NMOSD, researchers have been continuously exploring how to establish the ideal model. In this process, two key issues arise: 1) how the AQP4 antibody crosses the blood-brain barrier, and 2) the source of the AQP4 antibody. These two factors are critical for the successful development of rodent models of NMOSD. This paper reviews the current state of research on these two aspects.